The Effect of Power Training Variations on Increasing Leg Muscle Power and Smash Results in Volleyball PBV.UMA - Agung Julifer Hasugian; Irwansyah Siregar (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
This study aims to determine the effect of variations in power training on increasing leg muscle power of PBV.UMA volleyball athletes in 2020. To determine the effect of variations in power training on increasing smash results of PBV.UMA volleyball athletes in 2020. This study was carried out at the training location, namely the PBV field. .UMA Medan Area. This research was conducted from 04 February 2020 to 15 March 2020 starting at 16.00 WIB. The research method used is the experimental method. Sampling is done by means of purposive sampling (sample considerations) as many as 12 people. The results of the first study obtained T-Calculation of 17.36 and the t-distribution list using probability 1 – 1⁄2α = 0.975 with dk n – 1 = 11 obtained the value of t _((0.975)) = 2.2. In the hypothesis testing criteria it is stated that at t _count > t _table with = 0.05, then H_(0 ) is rejected, H_a is accepted where 17.36 > 2.2. The results of the second study obtained a T-Calculation of 7.83 and a t-distribution list using probability 1 – 1⁄2α = 0.975 with dk n – 1 = 11, the value of t _((0.975)) = 2.2. In the hypothesis testing criteria it is stated that at t _count > t _table with = 0.05, then H_(0 ) is rejected, H_a is accepted, where 7.83 > 2.2. Conclusion of research results There is a significant effect of variations in power training on increasing leg muscle power of PBV.UMA athletes in 2020. There is a significant effect of variations in power training on smash results of PBV.UMA athletes in 2020.